2017
DOI: 10.17576/mjas-2017-2103-14
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Oilfield Wastewater Treatment Using Membrane Filtration Over Conventional Technology

Abstract: The oil and gas industry has been a constant developing industry as it is of importance to the maintenance of industrial civilization in its current configuration and play vital roles in many other industries. Some oil and gas industry operations have been accountable of water contamination through by-results of refining and oil slicks. One of the biggest by-products that have raised a critical environment concern is oilfield produced water. Oilfield produced water (OPW) is coproduced aqua liquid phase which o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Similar results have been reported by previous researchers, for example, Zarghami et al [3], who incorporated polydopamine as an additive in a PES membrane and the modified membrane showed up to a 79% improvement in the flux recovery [50]. Another study done by Alkindy et al [4] has also reported a 38% flux recovery improvement for PES modified with GO/SiO 2 nanoparticles [31]. In contrast with MMMs incorporated with HNT-HFO, the flux recovery of the highest loading has surpassed the percentage of those in the previous study, with the highest flux recovery percentage of 90%.…”
Section: Antifouling Performance Of the Membranessupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results have been reported by previous researchers, for example, Zarghami et al [3], who incorporated polydopamine as an additive in a PES membrane and the modified membrane showed up to a 79% improvement in the flux recovery [50]. Another study done by Alkindy et al [4] has also reported a 38% flux recovery improvement for PES modified with GO/SiO 2 nanoparticles [31]. In contrast with MMMs incorporated with HNT-HFO, the flux recovery of the highest loading has surpassed the percentage of those in the previous study, with the highest flux recovery percentage of 90%.…”
Section: Antifouling Performance Of the Membranessupporting
confidence: 88%
“…This includes the increased permeability or selectivity, decreased fouling and elimination of unique pollutants accomplished by integrating two or more processes or by developing an optimized filtration method [2]. It could give the physicochemical stability of one element, while offering the optimal morphology with increased hydrophilicity and enhanced resistance to fouling and mechanical, chemical and thermal stability over a broader pH and temperature spectrum [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…High membrane cost, requirement of resin fouling, resin regeneration [22,23] Coagulation and flocculation Settling and dewatering of sludge High cost, large consumption of chemicals [24,25] Membrane filtration [7,30] The majority of these methods [7,[18][19][20][21][22][23][24][25][26][27][28][29][30] are expensive, ineffective in certain concentrations, or time-consuming, and adsorption is limited by the cost of the adsorption material [1,[6][7][8][9]31,32]. For these reasons, the choice of sorbent is crucial for the development of a simple, efficient, inexpensive, and environmentally friendly water purification method [33,34].…”
Section: Advantages Disadvantages Referencementioning
confidence: 99%
“…Produced water (PW) is a term used in the oil and gas industry to describe the aqueous liquid phase produced from wells during the extraction of oil and gas [1]. PW is the largest source of contaminated water discharged from oil and gas production operations [2] and on a global scale the production rate is 25-39.5 Mm 3 day −1 .…”
Section: Produced Water (Pw)mentioning
confidence: 99%